2021
DOI: 10.1080/03639045.2021.1935996
|View full text |Cite
|
Sign up to set email alerts
|

Topical NSAIDs for acute local pain relief: in vitro characterization of drug delivery profiles into and through human skin

Abstract: Objective: The efficacy of topical nonsteroidal anti-inflammatory drugs (NSAIDs) relates not only to the individual NSAID used but also to differences in formulation design. The aim of this study was to investigate the fundamental differences in ibuprofen and diclofenac drug delivery vehicles, specifically gels and plasters, compared to a recently launched 200 mg ibuprofen medicated plaster and characterize the resulting dermatologic-pharmacokinetic profiles into and through ex vivo human skin layers. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The observed faster permeability of ibuprofen agrees with previously observed results. 7 , 8 In a recent paper by Pradal, 7 it is suggested that the higher potency of diclofenac would result in a significantly higher values of “modified index of anti-inflammatory activity” for the diclofenac products in-spite of the lower permeation rates versus ibuprofen (around 10 fold increase for diclofenac). However, another recent paper by Wade et al 14 compared 1% diclofenac gel with 5% ibuprofen gel and 5% ibuprofen/3% menthol gel in a clinical trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed faster permeability of ibuprofen agrees with previously observed results. 7 , 8 In a recent paper by Pradal, 7 it is suggested that the higher potency of diclofenac would result in a significantly higher values of “modified index of anti-inflammatory activity” for the diclofenac products in-spite of the lower permeation rates versus ibuprofen (around 10 fold increase for diclofenac). However, another recent paper by Wade et al 14 compared 1% diclofenac gel with 5% ibuprofen gel and 5% ibuprofen/3% menthol gel in a clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…These include concentration of drug, the drug properties, specific salt used and the formulation. 7 , 8 However, most topical NSAID drug delivery results in lower systemic levels of drug when compared to recommended oral doses. 9 , 10 Therefore, higher permeation is generally desired to maximise the anti-inflammatory effect of topically applied NSAIDs.…”
Section: Introductionmentioning
confidence: 99%
“…Opting for NSAIDs in cream or gel formulation stands out as a preferred approach for managing OA, especially among the elderly. While these topicals may exhibit a slower absorption rate, their pharmacological activity is comparable to oral alternatives [157,158]. Their use is recommended by the main international guidelines for knee and hand OA treatment according to superior safety profile.…”
Section: Pharmacological Treatments In Oa 421 Nonsteroidal Anti-infla...mentioning
confidence: 99%